The Influence of Waste Banks on Waste Management Behavior and Customer Family Income - Ivakdalam, Lydia M.; Tupamahu, Yonette Maya; Watruty, Stefen P. (Agrikan Jurnal Agribisnis Perikanan, 2024)
Alstonia Waste Bank and Lestari Maluku Waste Bank are the first waste banks in Ambon City and are pilot waste banks. The two banks received CSR assistance from Pegadaian for the Alstonia waste bank and the Mandiri waste bank from CSR Pertamina. Waste management starting from the source that produces the waste can reduce the government's burden in terms of transportation and providing a place for disposal. The results of the research show that the waste processing techniques of the two waste banks are slightly different from the type of deposit every day and once a week at the Bumi Lestari Waste Bank. The amount of rupiah will be smaller if the waste deposited has not been sorted, but is still received. For the family income indicator based on a comparison of respondents' income using averages and data per individual, the results obtained are not much different. Waste banks do not make a large contribution to respondents' household income. This is influenced by several factors such as: intensity of saving, type of waste saved, weight of waste deposited, purchase price by the waste bank, and the respondent's household income. The percentage of additional income is higher, namely 1.15% and 3.01%. The more often customers save at a waste bank, the faster their savings can increase.